A Novel Approach to Augmenting Allograft Hamstring Anterior Cruciate Ligament Reconstructions Utilizing a Resorbable Type I Collagen Matrix with Platelet Rich Plasma. (11th March 2021) - Millan, Sean Mc; Thorn, Danielle; Ford, Elizabeth
Abstract : Background . Anterior cruciate ligament reconstruction (ACLR) is one of the most common lower extremity orthopedic surgeries performed in the United States. Annually, between 100, 000 and 200, 000 ACL tears affect 1 in 3, 000 people. The selection of autograft versus allograft for ACLR has been widely discussed in terms of risk of graft failure. Allograft reconstructions have been shown to have higher rerupture rates. One factor contributing to this risk is delayed biologic graft incorporation. Methods . A retrospective review was performed examining 14 patients who underwent an augmented quadruple-stranded hamstring allograft ACLR with a type I resorbable collagen matrix impregnated with platelet-rich plasma (PRP). Results . Within our clinical practice, the augmentation of quadruple-stranded hamstring allograft ACLR with a type I resorbable matrix impregnated with PRP has yielded good early clinical success at 2-year outcomes (N = 14 ). Zero ACLR failures have been reported to date in this series. Conclusion . This case series offers a novel approach for soft tissue allograft ACLR augmented with a type I collagen matrix impregnated with PRP. The authors theorize that this augmentation may improve biologic graft incorporation into the host bone tunnels.